Evidence of increased cardiovascular disease risk in left-handed individuals - Simon, Abigayle B.; Norland, Kimberly; Blackburn, Marsha; Zhao, Sumang; Wang, Xiaoling; Harris, Ryan A. (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Approximately 10% of the world is left-handed (LH). Research suggests that LH individuals may have shorter lifespans compared to right-handed (RH) individuals. LH individuals also appear to have more cardiovascular disease (CVD) related conditions like diabetes and cancer. Thus, the present study sought to test the hypothesis that vascular function and heart rate variability (HRV), both key indicators of CVD risk, would be lower in LH compared to RH individuals. METHODS: 379 participants, 18-50 years old, were enrolled. Flow-mediated dilation (FMD), a bioassay of vascular endothelial function and standard deviation of R-R interval (SDNN), a parameter of HRV, were evaluated as indices of CVD risk. Data are reported as mean±SD. RESULTS: 12.1% of the participants were LH. No differences in demographics or clinical laboratory values were observed between groups, except high-density lipoprotein (HDL) was higher (p=0.033) in RH. FMD was significantly (p=0.043) lower in LH (6.1±3.2%) compared to RH (7.6±3.8%), independent of age, sex, race, BMI, and HDL. Total power (p=0.024) and lowfrequency power (p=0.003) were lower in LH compared to RH. Additionally, SDNN was lower (p=0.041) in LH (47.4±18.8ms) compared to RH (54.7±22.3ms). A negative correlation between FMD and mean arterial pressure (r=-0.517; p<0.001) was observed in LH; no relationships were observed in RH (all p>0.05). CONCLUSION: Vascular endothelial function and HRV are lower in LH compared to RH. In addition, relationships between FMD and traditional CVD risk factors were only observed in LH. These data support an increased risk of CVD in LH.